Photonic Sensors - RAO, Yunjiang
Photonic Sensors publishes original, peer-reviewed articles that report on new developments of interest to both the photonics and sensor communities in all fields of photonic sensing science and technology. Topics include optical fiber sensors, planar waveguide sensors, laser-based sensors, and biophotonic sensors, etc. Photonic Sensors focuses on experimental contributions related to novel principles, structures or materials for photonic sensors. Papers that report on investigations based on combinations of experimental and analytical/numerical approaches are also welcome. In addition to research articles, Photonic Sensors publishes letters and review articles. Letters provide an opportunity to rapidly disseminate research results that are of timely interest to the photonic sensor community. Upon submission, letter manuscripts should be accompanied by a brief justification for rapid publication. Letters should not exceed four journal pages. Review articles provide readers with comprehensive reviews of emerging topics, topics of critical importance or activities of world-class research groups and can be either solicited or non-solicited. Review articles appear on a regular basis.